2023
DOI: 10.1186/s13578-023-00977-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming in colorectal cancer: regulatory networks and therapy

Abstract: With high prevalence and mortality, together with metabolic reprogramming, colorectal cancer is a leading cause of cancer-related death. Metabolic reprogramming gives tumors the capacity for long-term cell proliferation, making it a distinguishing feature of cancer. Energy and intermediate metabolites produced by metabolic reprogramming fuel the rapid growth of cancer cells. Aberrant metabolic enzyme-mediated tumor metabolism is regulated at multiple levels. Notably, tumor metabolism is affected by nutrient le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 228 publications
0
12
0
Order By: Relevance
“…Previous studies have demonstrated that cancer cell metabolism is impaired, and metabolic rewiring of CRC cells can alter the expression of critical energy metabolites, which leads to proliferation and spreading to other organs. 6 These findings line up with the decreased levels of circulating glycerophospholipids (lysophosphatidylcholines [LysoPCs] and lysophosphatidylethanolamines [LysoPEs]), taurine and hypoxanthine found in recurrent patients with CRLM (Table 1). A possible explanation could be (1) a rapid clearance of LysoPC from the circulation for the synthesis of phosphatidylcholine (the most abundant phospholipid of mammalian cell types in the liver); (2) a high demand of energy for cell membrane-remodelling during cancer proliferation, previously reported as a shift of LysoPC concentrations between cancer tissue and blood 7 ; (3) a higher demand for hypoxanthine by an up-regulated purine metabolism typically associated with cellular differentiation and aggressiveness.…”
mentioning
confidence: 62%
“…Previous studies have demonstrated that cancer cell metabolism is impaired, and metabolic rewiring of CRC cells can alter the expression of critical energy metabolites, which leads to proliferation and spreading to other organs. 6 These findings line up with the decreased levels of circulating glycerophospholipids (lysophosphatidylcholines [LysoPCs] and lysophosphatidylethanolamines [LysoPEs]), taurine and hypoxanthine found in recurrent patients with CRLM (Table 1). A possible explanation could be (1) a rapid clearance of LysoPC from the circulation for the synthesis of phosphatidylcholine (the most abundant phospholipid of mammalian cell types in the liver); (2) a high demand of energy for cell membrane-remodelling during cancer proliferation, previously reported as a shift of LysoPC concentrations between cancer tissue and blood 7 ; (3) a higher demand for hypoxanthine by an up-regulated purine metabolism typically associated with cellular differentiation and aggressiveness.…”
mentioning
confidence: 62%
“…We then identified 32 statistically significant peaks in RS using a Student’s t -test with the false discovery rate correction and corresponding metabolites that differentiated OX-treated cells from untreated control (Figure e); 28 of these metabolites decreased in the treatment group and 4 metabolites increased. To associate RS spectral data with specific metabolites and metabolite classes, we referred to the cited literature in Table that reports well-established RS peaks for key metabolites. Tentative peak assignments were narrowed down based on literature on metabolites that are impacted in human CRC and cellular metabolites that change in response to treatment; these literature evidence supported the assigned Raman peaks to the metabolites we have listed. , As each RS peak arises from vibrational modes within a functional group, a specific peak is not exclusive to a metabolite. Therefore, our tentative peak assignments represent the most plausible major metabolites that contribute to these peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both glucose (sugar) and amino acids contribute to amino sugar formation. Meanwhile, metabolism of both glucose and amino acids plays a key role in colorectal cancer development (Zhang et al, 2023). Possibly, our finding of increased potential metabolism of amino sugars with colorectal cancer may reflect dysregulated activity of glucose and amino acids with the product of their interaction (amino sugars) recorded by the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%